Research on a High Precision Reservoir Flood Regulating Calculation Based on Solving Integral Equation - ZHOU Bin (Renmin Zhujiang)
Reservoir flood regulating calculation can be divided into two methods: solving ordinary differential equation and solving integral equation, of which the method of solving integral equation is more widely used in engineering. At present, trapezoidal method is widely used in engineering to calculate the outflow volume, which has relatively low calculation accuracy of outflow volume, a certain influence on the accuracy of results and a space for improvement. With flood regulating ordinary integral equation and differential equation, cubic Hermite polynomial is constructed to fit the outflow process, outflow volume is calculated by Simpson integral method, and a new reservoir flood regulating integral equation can be constructed, through which the calculation result of outflow volume can reach cubic algebraic precision. The new reservoir flood regulating integral equation and its error transfer equation add the influence term of cubic Hermite polynomial fitting to the original equation, which is an improvement of the traditional reservoir flood regulating integral equation. After the flood regulating calculation is conducted for engineering at different flood regulating periods, the results show that the new equation has certain improvement on calculation accuracy, which can be applied by engineering technicians for reference.